1999
DOI: 10.1097/00005537-199905000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Association of vascular endothelial growth factor expression with angiogenesis and lymph node metastasis in nasopharyngeal carcinoma

Abstract: These results suggest that VEGF plays an important role in lymph node metastasis through induction of angiogenesis in NPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 22 publications
4
56
0
Order By: Relevance
“…We also have reported that vascular endothelial growth factor (VEGF) could be an important regulator of angiogenesis in NPC tissue [28,29,30]. In addition to these studies, we reported LMP1 induces VEGF through HIF1α using epithelial cell lines [31].…”
Section: Discussionmentioning
confidence: 67%
“…We also have reported that vascular endothelial growth factor (VEGF) could be an important regulator of angiogenesis in NPC tissue [28,29,30]. In addition to these studies, we reported LMP1 induces VEGF through HIF1α using epithelial cell lines [31].…”
Section: Discussionmentioning
confidence: 67%
“…Tumor cells then pass through the junctions between blood and lymphatic circulations and can be arrested in the lymph node. Previously, we reported a relationship between angiogenesis and the progression of regional lymph node metastasis in NPC [6,22] . We also showed that an EBV-encoded oncoprotein, LMP1, plays a key role in anigiogenesis through the induction of angiogenic factors including FGF-2, IL-8, and VEGF-A [6-8, 22, 28-30] .…”
Section: Discussionmentioning
confidence: 90%
“…Tumor angiogenesis is induced by increased secretion of angiogenic factors and by down-regulation of angiogenic inhibitors [5] . Previously, we showed a significant relationship between angiogenesis and advancement of nodal status in NPC tissues [6,7] . Furthermore, we reported that latent membrane protein 1 (LMP1), an EBV-associated oncoprotein, induces angiogenic factors including vascular endothelial growth factor (VEGF)-A, interleukin (IL)-8, and fibroblast growth factor (FGF)-2 [6][7][8] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…VEGF induces the proliferation, differentiation, and migration of vascular endothelial cells; increases the permeability of the capillaries; and enhances the survival of endothelial cells by preventing their apoptosis (Ferrara and Davis-Smyth, 1997;Gupta et al, 1999;Kyzas et al, 2004). It is suggested that VEGF plays an important role in lymph node metastasis through induction of angiogenesis in primary nasopharyngeal carcinomas (Wakisaka et al, 1999).…”
Section: Introductionmentioning
confidence: 99%